ChemInform Abstract: Emerging Energy and Environmental Applications of Vertically‐Oriented Graphenes. Issue 25 (5th June 2015) - Bo, Zheng; Mao, Shun; Jun Han, Zhao; Cen, Kefa; Chen, Junhong; Ostrikov, Kostya (Ken)
Abstract: Review: tutorial review on plasma synthesis of vertically‐oriented graphenes, growth mechanism, and properties for energy and environmental applications; 50 refs.